Anti-Melanogenic Activity of Calocedrus formosana Wood Essential Oil and Its Chemical Composition Analysis - Hsiao, Wen-Wei; Kumar, K. J. Senthil; Lee, Hui-Ju; Tsao, Nai-Wen; Wang, Sheng-Yang (Plants (Basel), 2021)
Calocedrus formosana (Cupressaceae) is one of the five precious woods of Taiwan. In this study, we investigated the anti-melanogenic activity of C. formosana wood essential oil (CFEO) and its bioactive components in vitro. Initially, CFEO exhibited strong mushroom tyrosinase activity in the cell-free mushroom tyrosinase assay system with an IC50 value of 2.72 µg/mL. Next, treatment with CFEO significantly as well as dose-dependently reduced a combination of α-melanocyte-stimulating hormone and forskolin (α-MSH-FSK)-induced melanin synthesis in B16-F10 cells. Indeed, 80 μg/mL CFEO completely inhibited melanin production, which is similar to that of control cells. Further studies revealed that treatment with CFEO significantly inhibited melanogenesis regulatory proteins, including TRP-1, TRP-2, and MITF, whereas tyrosinase was unaffected by either α-MSH-FSK or CFEO. In addition, the composition of the CFEO was characterized. The major components of CFEO were α-terpineol (23.47%), shonanic acid (10.45%), terpinen-4-ol (12.23%), thymol (5.3%), piperitone (3.44%), berbenone (2.81%), thujic acid (1.65%), and chaminic acid (0.13%). Among them, shonanic acid (1), thujic acid (2), and chaminic acid (3) were uncommon constitutes in essential oils, which could be the index compounds of CFEO, and the structure of these compounds were confirmed by spectral analysis. Furthermore, we found that thymol is an active ingredient responsible for CFEO’s anti-melanogenic activity. Based on these results, we suggest that CFEO or thymol could be a potential candidate for the development of skin whitening products for cosmetic purposes.